Why the earth quakes - Levy, Matthys; Salvadori, Mario 1907-1997; Lilly, Michael (New York, NY W. W. Norton & Company, Inc., 1997)
Stories of the worst natural disasters involving volcanoes and earthquakes in Lisbon, San Fransisco, Alaska, Vesuvius, Krakatau, and Mt St. Helens - Modern building technologies - Tectonic plates - Big bang - Black holes.
Cracked egg -- Fire goddess -- Mountains of Vulcan -- Lisbon, 1755 -- Birth of seismology -- Measuring earthquakes -- Kanto earthquake -- Resisting earthquakes -- Great fault -- Three minutes in Anchorage -- Precursors and predictions -- Seismic isolation -- Social consequences: Codes and public policy -- Risk and preparedness -- Echoes of the big bang.
Includes bibliographical references and index.
Keywords: Volcanoes; Earthquakes